1998
DOI: 10.2337/diacare.21.10.1694
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glycemic Control in Intensively Treated Type 1 Diabetic Patients Using Blood Glucose Meters With Storage Capability and Computer-Assisted Analyses

Abstract: Use of a meter with memory in conjunction with computer-generated analyses of stored blood glucose test results can lead to improved glycemic control when used by a group of intensively treated adult diabetic patients. Improvement in glycemic control was related to frequency of blood glucose testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 18 publications
1
34
0
2
Order By: Relevance
“…Research has shown that increased SMBG is associated with improved glycemic control. 23 This is possible as adjustments in pharmacotherapy can be done based on blood glucose levels so as to achieve adequate glycemic control. Hence, it is important that patients be made aware about the importance of SMBG and encouraged to follow it as recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that increased SMBG is associated with improved glycemic control. 23 This is possible as adjustments in pharmacotherapy can be done based on blood glucose levels so as to achieve adequate glycemic control. Hence, it is important that patients be made aware about the importance of SMBG and encouraged to follow it as recommended.…”
Section: Discussionmentioning
confidence: 99%
“…24 Automatic recording systems can be helpful, such as glucometers with built-in memory chips and cameras with digital images that can retrieve years of past data. 25 Communication strategies that include electronic messaging can also provide an unambiguous method to return long afterwards to check what was and was not mentioned. 26,27 Another corrective strategy is to write down during the initial patient contact the specific expectations that are intended at the time of subsequent follow-up.…”
Section: Unwanted Forgetfulnessmentioning
confidence: 99%
“…There are many reasons that vary from individual to individual, but it is clear that the tools today do not easily allow for the normalization of glycemia for patients lacking b-cell function. Self-monitoring of blood glucose levels (27), continuous subcutaneous insulin infusion (28), CGM (18), and now low-glucose suspend (LGS) pumps (29) have all been demonstrated to significantly improve glycemic control either by reducing A1C or hypoglycemia levels. However, wide glucose excursions above and below the target range persist in almost all patients and attempts to achieve tighter and tighter glycemic control take more and more effort with diminishing returns.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%